Robotic-assisted partial nephrectomy without using ureteral stent: a single center experience - Ozkan, Burak; Coskuner, Enis Rauf; Yalcin, Veli (AVES, 2016)
Objective: To share our results of robotic assisted partial nephrectomy (RAPN) we performed without using ureteral stent in a single center from Turkey. Material and methods: Medical records of consecutive 45 patients (34 men and 11 women) who underwent RAPN for kidney lesions between March 2011 and December 2014 were retrieved, and evaluated. All the procedures were performed by a transperitoneal approach without using ureteral stent prior to surgery. Renal artery clamping was used in all cases and intraoperative ultrasonography was used in 2 cases. Results: Patients undergoing RAPN had a mean tumor size of 4.42 cm (2-8) and a mean renal nephrometry score of 5.82 (4-11). The mean estimated blood loss was 250 mL (150-450 ml) and the mean operative time was 195 minutes (150-300). There was no statistical difference between the preoperative and postoperative serum creatinine levels at the first follow-up visit (0.9 vs. 0.95, p= 0.087). Surgical margin positivity was not detected in any patient, and the mean surgical margin distance was calculated as 0.4 mm (0.2-10). In only 1 patient disease recurrence was detected at the 21st month of the the follow-up period, and no distant metastases was reported in our patients at a mean follow-up of 10 months (3-36 mos). Our complication rate was 11.1\% and according to the Clavien system complications were as

grade 2 (3 patients), grade 3a (1 patient) and grade 3b (1 patient). Conclusion: With appropriately selected patients and adequate surgical experience, RAPN performed without using ureteral stent is a safe and feasible method for localized renal tumors.
Keywords: Kidney cancer; partial nephrectomy; robotic-assisted partial nephrectomy; ureteral